PENGAGIHAN ZAKAT OLEH INSTITUSI ZAKAT DI MALAYSIA: MENGAPA MASYARAKAT ISLAM TIDAK BERPUAS HATI? - Wahid, Hairunnizam (Jurnal Syariah, 2009)
Zakat institution; as an intermediary entity between zakat payers and zakat receivers plays an important role in collecting and distributing zakat efficiently. However, zakat payers are dissatisfied with the performance of the zakat institution. This study examines the dissatisfaction effect of zakat payers’ towards their zakat payments and investigates the reasons for this situation. This study utilises and analyses primary data of dissatisfied zakat payers and potential zakat payers in Peninsular Malaysia by using descriptive analysis and logistic regression. The results show that more than half of the dissatisfied payers do not pay zakat which would have led to a decrease in potential zakat collection. Nevertheless, there is no significant difference between the dissatisfaction level of zakat Institutions at the State level; that may or may not be a private organisation. The result further shows that the main reasons for zakat payer’s dissatisfaction are ineffective distribution methods and insufficient dessimination of information on zakat distribution. This study therefore proposes several measures to overcome the weaknesses identified; hence to increase the satisfaction of zakat payers and to encourage Muslims to pay zakat through authorized zakat institutions.